Body Mass Index and Thyroid Function Tests in Male Adults in Mosul City - Taher, Ayman M.; Mohammed, Hazim A. (Journal for Research in Applied Sciences and Biotechnology, 2024)
The relationship between thyroid gland and body mass index (BMI) is a subject of growing interest. Thyroid hormones' impact on metabolism directly affects energy expenditure which is in turn affect weight balance. Subjects and Method: This study occurred in Mosul city in the north of Iraq, between December 2022 - June 2023, and it comprised one hundred adult males ranging in age from 20 - 60 years. Participants had to be apparently healthy men with appropriate thyroid functions, according to the inclusion criteria. Individuals who used specific medicines known for altering thyroid functions were excluded, those who have positive anti-thyroid peroxidase antibodies (ATPO), a personal or familial history of thyroid diseases, and medical illnesses such as hypertension, diabetes, and cardiac, renal, and liver diseases. The thyroid parameters that’s measured to the subjects were triiodothyronine (FT3), thyroxine (FT4) using immuno-enzymatic competitive assays and Thyroid stimulating hormone (TSH) by two-site immuno-enzymatic (sandwich) method. Results: found no significant relationships between BMI and other thyroid function FT3 no significant increase TSH, on the contrary increased across BMI classes, moreover FT4 decreased. Conclusion: this work showed that the thyroid function of the different BMI groups under investigation showed no significant change.